An Accidental Purpose: The Impact of the First World War on University College Nottingham - Noble, Michael J (2023)
This thesis examines the impact that the First World War had on the development of University College Nottingham. It makes the hypothesis that the college was, like comparable educational institutions, following a particular path of development by the early twentieth century and that the outbreak of war permanently altered the circumstances in which the college operated and changed this trajectory of development. It contends that the war had significant and lasting effects on the college while it was in a relatively early phase of development, being less than forty years old by the time that the Armistice was effected, and that the occurrence of the war at this stage of the college’s growth was significant. Certain developmental goals, most notably the grant of a royal charter establishing full university status, were, by necessity, placed on hold, while other ambitions, such as a proposed merger with other institutions to found an East Midlands University, were disrupted and ultimately abandoned completely. Other impacts, which also affected similar institutions in other English towns, ultimately led to the development of a national system of higher education and research in the UK and altered the position that such institutions had in British society and its economy. The thesis examines the development of this national system and Nottingham’s place in it.